2015
DOI: 10.1089/lap.2014.0051
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-Assisted Ureteral Re-implantation: A Case Series

Abstract: RAUR is a safe and effective procedure. Extensive laparoscopic lysis of adhesions represents the primary challenge to an otherwise straightforward minimally invasive surgery. At our institution, RAUR has replaced open ureteral re-implantation as the preferred treatment for benign mid-/distal ureteral stricture disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 16 publications
0
9
0
3
Order By: Relevance
“…On review of the literature we identified 17 studies ( Table 5 [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] ) evaluating distal ureteric reconstructive surgery, with institutions presenting their experience using a number of differing techniques including uretero-ureterostomy and uretero-neocystostomy (often with adjunct procedures such as Boari flap formation or Psoas hitch).…”
Section: Robot-assisted Distal Ureteric Reconstructionmentioning
confidence: 99%
“…On review of the literature we identified 17 studies ( Table 5 [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] ) evaluating distal ureteric reconstructive surgery, with institutions presenting their experience using a number of differing techniques including uretero-ureterostomy and uretero-neocystostomy (often with adjunct procedures such as Boari flap formation or Psoas hitch).…”
Section: Robot-assisted Distal Ureteric Reconstructionmentioning
confidence: 99%
“…All selected studies had a retrospective nature. From them, eight were case series [ 2 , 4 , 5 , 16 20 ] and four had comparative study design comparing RAL and open approaches (two articles) [ 7 , 21 ], two different RAL techniques (one article) [ 6 ], as well as RAL, laparoscopic and open surgeries (one article) [ 22 ]. Review and analysis of the last article data were performed only in RAL and open groups [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The improved intracorporeal suturing makes ureteral surgery a logical extension, based on the experience with anastomoses in a prostatectomy operation [ 4 , 5 ]. RAL is currently used in numerous urologic procedures, including ureteral reconstruction, leading to a decreased morbidity and better clinical outcomes when compared to open surgery [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, most robotic series have adopted nontunnelled reimplantation, which is unsurprising as this is far less technically challenging. Therefore, in adult patients undergoing a robotic ureteric reimplantation, limited data from case series suggest the feasibility and safety of this approach [11,12]. There is a need for studies to clarify this issue.…”
Section: Evidence Acquisitionmentioning
confidence: 99%